Recent Progress of Pre-targeting Methods in the Fight Against Breast Cancer - Sun, Zhi-Gang; Song, Yu-Cui; Li, Zhi-Na; Zhang, Zhi-Guo (International Journal of Innovative Research in Medical Science, 2024)
Breast cancer is a malignant tumor that seriously affects women's physical and mental health. Drug resistance and side effects pose challenges to targeted treatment of breast cancer. In recent years, there have been many studies on pre-targeting technology in the treatment of various diseases. This article reviews the recent research progress of pre-targeting technology in the fight against breast cancer.